A decision model for selecting parts feeding policies in assembly lines. Issue 6 (13th July 2015) - Caputo, Antonio C.; Pelagagge, Pacifico M.; Salini, Paolo
Abstract : Purpose: – The purpose of this paper is to develop an optimization model allowing the choice of parts feeding policy to assembly lines in order to minimize total cost. Design/methodology/approach: – An integer linear programming mathematical model is developed to assign the optimal material feeding policy to each part type. The model allows choice between kitting, line stocking and just in time delivery policies. Findings: – The choice of assembly lines feeding policy is not trivial and requires a thorough economic comparison of alternatives. It is found that a proper mix of parts feeding policies may be better that adopting a single material delivery policy for all parts. Research limitations/implications: – The model is aimed at single-model assembly lines operating in a deterministic environment, but can be extended to the multi-model line case. While relevant quantitative cost drivers are included, some context-related qualitative factors are not included yet. The model assumes that information about product structure and part requirements are known and that a preliminary design of the assembly system has been carried out. Practical implications: – Production managers are given a quantitative-decision tool to determine the optimal mix of material supply policies at an early decision stage. Originality/value: – Respect previous simplified literature models, this approach allows to quantify a number of additional factors which are critical for successful implementation of cost-effective parts feeding systems, allowing comparison of alternative policies on a consistent basis.